Does motivation matter? The influence of the agency perspective on temporary agency workers. Issue 4 (5th June 2017) - Chen, Pei-Chen; Wang, Ming-Chao; Fang, Shih-Chieh
Abstract : Purpose: Based on agency perspective on temporary agency workers, the purpose of this paper is to explore the relationship between firms' agency problems and agency cost on agency workers; moreover, intrinsic motivation and extrinsic motivation are considered in seeking to understand how they moderate this relationship. Design/methodology/approach: Using the Hsinchu Science Park directory of corporate affiliations as a sample frame, the authors adopted a paired questionnaire which included two parts in order to consider the possible problem of common method variances. The first part is completed by the manager of the firms and the second part is completed by his/her temporary agency workers. Finally, 94 firms completed questionnaires, providing a total sample of 94 R&D managers and 458 temporary agency workers. The rate of participation was 31.65 percent. Findings: Using a questionnaire survey of 94 high-tech firms, from which a total of 94 R&D managers and 458 temporary agency workers participated, the results show that firms' agency problems have a positive influence on the agency cost of monitoring temporary agency workers. In addition, while this relationship is negatively moderated by extrinsic motivation, intrinsic motivation has a non-significant moderating effect. Originality/value: The managers of firms should consider not only the short-term flexibility of employing temporary agency workers, but also the long-term cultivation of promoting great agency workers. This could maximize the efficiency of the interaction between intrinsic motivation and extrinsic motivation. Of course, the firms should think about how to reduce the agency problems created by goal conflict, information asymmetry and risk sharing with temporary agency workers, because this could also provide a chance for the firms to decrease agency costs spent on monitoring.